Neuron-to-glia and glia-to-glia signaling directs critical period experience-dependent synapse pruning - Nelson, Nichalas; Miller, Vanessa; Broadie, Kendal (Frontiers in Cell and Developmental Biology, 2025)
Experience-dependent glial synapse pruning plays a pivotal role in sculpting brain circuit connectivity during early-life critical periods of development. Recent advances suggest a layered cascade of intercellular communication between neurons and glial phagocytes orchestrates this precise, targeted synapse elimination. We focus here on studies from the powerful Drosophila forward genetic model, with reference to complementary findings from mouse work. We present both neuron-to-glia and glia-to-glia intercellular signaling pathways directing experience-dependent glial synapse pruning. We discuss a putative hierarchy of secreted long-distance cues and cell surface short-distance cues that act to sequentially orchestrate glia activation, infiltration, target recognition, engulfment, and then phagocytosis for synapse pruning. Ligand-receptor partners mediating these stages in different contexts are discussed from recent Drosophila and mouse studies. Signaling cues include phospholipids, small neurotransmitters, insulin-like peptides, and proteins. Conserved receptors for these ligands are discussed, together with mechanisms where the receptor identity remains unknown. Potential mechanisms are proposed for the tight temporal-restriction of heightened experience-dependent glial synapse elimination during early-life critical periods, as well as potential means to re-open such plasticity at maturity.